Bonded body and ceramic copper circuit board
By implementing a bonding body with a controlled titanium distribution in the bonding layer, the TCT characteristics of ceramic copper circuit boards are improved, addressing the issue of deteriorating performance with increased bonding body size.
Patent Information
- Application Number
- JP2025023768
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2020-07-27
- Filing Date
- 2025-02-17
- Publication Date
- 2025-04-30
- Estimated Expiration
- 2041-05-17
AI Technical Summary
The distribution of titanium (Ti) in the bonding layer of ceramic copper circuit boards affects the temperature cycling test (TCT) characteristics, with existing technologies experiencing deterioration in TCT properties as the bonding body grows.
A bonding body structure is developed with a silicon nitride substrate, a copper plate, and a titanium-based bonding layer. The bonding layer has a first region at the interface with the silicon nitride substrate and a second region between the first region and the copper plate, with controlled Ti concentrations and variations to achieve a specific Ti concentration ratio and uniformity.
The controlled Ti distribution in the bonding layer improves the TCT characteristics of ceramic copper circuit boards, maintaining performance even as the bonding body size increases, and enhances the reliability of the bonding process.
Smart Images

Figure 2025069468000001_ABST
Abstract
Description
[Technical field]
[0001] The embodiments described below relate to a bonded body and a ceramic copper circuit board. [Background technology]
[0002] A bonded body of a ceramic substrate and a copper plate is used as a circuit board for mounting a semiconductor element or the like. International Publication No. 2018 / 021472 (Patent Document 1) discloses a ceramic copper circuit board in which a ceramic substrate and a copper plate are bonded. In Patent Document 1, a brazing material containing Ag, Cu, Ti, etc. is used for the bonding layer. In addition, the temperature cycle test (TCT) characteristics are improved by controlling the nanoindentation hardness of the bonding layer. In Patent Document 1, the nanoindentation hardness is controlled by having AgTi crystals or TiC present in the bonding layer. In Patent Document 1, the bonding strength and TCT characteristics are improved by controlling the nanoindentation hardness. On the other hand, as the size of the junction increased, the TCT properties decreased in some cases. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] International Publication No. 2018 / 021472 [Patent Document 2] Patent No. 4077888 Summary of the Invention [Problem to be solved by the invention]
[0004] When the cause of this was investigated, it was found that the cause was the Ti distribution in the bonding layer. Japanese Patent No. 4077888 (Patent Document 2) discloses a bonded body using an Ag-Cu-Ti brazing material. In Patent Document 2, a titanium nitride (TiN) layer is formed in the bonding layer. This titanium nitride layer is a hard layer with a Vickers hardness of about 1100 to 1300. It was found that the difference in hardness between the TiN layer and the AgCu layer was the cause. The present invention aims to provide a bonded body in which the Ti distribution in the bonding layer is controlled in order to solve such problems. [Means for solving the problem]
[0005] The bonded body according to the embodiment includes a silicon nitride substrate, a copper plate, and a bonding layer disposed on at least one surface of the silicon nitride substrate and bonding the silicon nitride substrate and the copper plate. The bonding layer contains titanium. The bonding layer includes a first region including a layer mainly composed of titanium, the layer being formed at an interface between the bonding layer and the silicon nitride substrate, and a second region located between the first region and the copper plate. When the Ti concentration in a range of 200 μm×thickness of each measurement region of the first region and the second region is measured by EDX, the ratio M1 / M2 of the titanium concentration M1 at% of the first region to the titanium concentration M2 at% of the second region is 0.5 or more and 5 or less. The titanium concentration M2 of the second region is within a range of 0.5 at% or more and 15 at% or less. When a plurality of the measurement regions are set in the second region and the Ti concentration of each measurement region is measured by EDX, the variation in Ti concentration between the plurality of measurement regions is within ±20%. [Brief description of the drawings]
[0006] [Figure 1] FIG. 2 is a diagram showing an example of a bonded body according to an embodiment. [Diagram 2] FIG. 4 is a diagram showing an example of a bonding layer of a bonded structure according to an embodiment. [Diagram 3] FIG. 2 is a diagram showing an example of a ceramic copper circuit board according to an embodiment. [Figure 4]2 shows another example of a ceramic copper circuit board according to an embodiment. [Diagram 5] 1 is a diagram showing an example of a semiconductor device according to an embodiment; DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0007] The bonded body according to the embodiment includes a silicon nitride substrate, a copper plate, and a bonding layer disposed on at least one surface of the silicon nitride substrate and bonding the silicon nitride substrate and the copper plate. The bonding layer contains titanium. The bonding layer includes a first region including a layer mainly composed of titanium, the layer being formed at an interface between the bonding layer and the silicon nitride substrate, and a second region located between the first region and the copper plate. When the Ti concentration in a range of 200 μm×thickness of each measurement region of the first region and the second region is measured by EDX, the ratio M1 / M2 of the titanium concentration M1 at% of the first region to the titanium concentration M2 at% of the second region is 0.5 or more and 5 or less. The titanium concentration M2 of the second region is within a range of 0.5 at% or more and 15 at% or less. When a plurality of the measurement regions are set in the second region and the Ti concentration of each measurement region is measured by EDX, the variation in Ti concentration between the plurality of measurement regions is within ±20%. Fig. 1 shows an example of a bonded body according to an embodiment. Fig. 2 shows an example of a bonding layer of a bonded body according to an embodiment. In Fig. 1 and Fig. 2, 1 is a bonded body. 2 is a ceramic substrate. 3 is a copper plate. 4 is a bonding layer. 5 is a first region. 6 is a second region. FIG. 1 shows a bonded body 1 in which two copper plates 3 are disposed on both sides of a ceramic substrate 2 with a bonding layer 4 therebetween. In the illustrated example, the length and width of the ceramic substrate 2 and the two copper plates 3 are the same. The bonded body according to the embodiment is not limited to this form, and may have a structure in which a copper plate is provided on only one side of the ceramic substrate 2. The length and width of the ceramic substrate 2 may be different from the length and width of the copper plate 3.
[0008] The bonded body 1 includes a ceramic substrate 2, a copper plate 3, and a bonding layer 4. The bonding layer 4 is disposed on at least one surface of the ceramic substrate, and bonds the ceramic substrate 2 and the copper plate 3. The bonding layer 4 contains Ti, and has a first region 5 and a second region 6. The first region 5 includes a layer mainly composed of titanium. The layer mainly composed of titanium is formed at the interface between the bonding layer 4 and the ceramic substrate 2. The second region 6 is located between the first region 5 and the copper plate. 2 shows a conceptual diagram of the bonding layer 4. The bonding layer 4 has a laminated structure of a first region 5 and a second region 6.
[0009] The first region 5 is a region including a layer mainly composed of titanium. The layer mainly composed of titanium refers to a region containing 30 at % or more of titanium. The layer mainly composed of titanium refers to a layer containing one or more of the following: titanium simple substance, oxide, nitride, silicide, and oxynitride. For example, when titanium silicide is formed on the titanium nitride layer in contact with the titanium nitride layer, the layer mainly composed of titanium silicide and the titanium nitride layer. In other words, when titanium silicide is directly in contact with the titanium nitride layer, the titanium nitride layer and titanium silicide are counted as a layer mainly composed of titanium. Moreover, the first region 5 exists along the interface between the ceramic substrate 2 and the bonding layer 4. Therefore, the layer containing titanium as a main component is formed along the surface of the ceramic substrate 2. The layer containing titanium as a main component is formed continuously in the thickness direction from the ceramic substrate 2. For example, titanium nitride present at a position away from the layer containing titanium as a main component is counted as the second region 6. When simple titanium, an oxide, or an oxynitride is present at a position away from the layer containing titanium as a main component, they are counted as the second region 6. Examples of Ti oxides include TiO2 (titanium oxide). Examples of Ti nitrides include TiN (titanium nitride) and Ti2N (titanium nitride). Examples of Ti oxynitrides include TiON (titanium oxynitride). Ti oxides, Ti nitrides, and Ti oxynitrides are not limited to the examples. For example, TiN (titanium nitride) has a stable stoichiometry where the atomic ratio of titanium to nitrogen is 1:1, but it may deviate from the stoichiometry. In addition, the layer mainly composed of titanium may be a layer in which two or more of the exemplified materials are mixed. "Titanium nitride" refers to a compound of titanium and nitrogen. When written as TiN, the atomic ratio of titanium to nitrogen is not limited to 1:1, and refers to a compound of titanium and nitrogen. In addition, when the ceramic substrate is a nitride-based ceramic substrate, the layer containing titanium as a main component contains titanium nitride as a main component. In addition, in the case of a nitride-based ceramic substrate, titanium nitride containing 30 at% or more of titanium constitutes the layer containing titanium as a main component. In addition, the titanium nitride may be present in one or more types selected from cubic crystals, hexagonal crystals, and tetragonal crystals. In addition, in the case of a nitride-based ceramic substrate, the first region 5 can be obtained based on the titanium nitride layer formed on the surface of the ceramic substrate 2. In other words, the titanium amount M1 of the first region 5 can be obtained using the maximum thickness of the titanium nitride layer. When the bonding layer 4 contains Ag, the layer mainly composed of titanium nitride is added with Ti2N, Ti 0.83 N 0.17 and metallic Ti. 0.83 N 0.17Alternatively, metallic Ti becomes a Ti-rich phase having a large amount of Ti. The presence of the Ti-rich phase in the layer mainly composed of titanium nitride makes it possible to control the amount of Ti present in the second region 6. In addition, when the bonding layer does not contain Ag, it is preferable that the Ti-rich phase is present in the layer mainly composed of titanium nitride in a range of 0 at% to 10 at%. Here, 0 at% of the Ti-rich phase means that it is below the detection limit. The Ti-rich phase contains more Ti than a region in which the atomic ratio of Ti to N is 1:1. By increasing the amount of Ti in the first region 5, it is possible to control the ratio of the titanium concentration in the first region 5 to the titanium concentration in the second region 6. In addition, when the ceramic substrate is an oxide-based ceramic, the layer containing titanium as a main component contains titanium oxide as a main component. Examples of titanium oxide include TiO2, TiO, and Ti3O2. Therefore, the layer containing titanium as a main component may be recognized based on the titanium oxide layer. The layer containing titanium as a main component is formed on the surface of the ceramic substrate 2. The layer containing titanium as a main component does not need to have a constant thickness in the surface direction. The layer containing titanium as a main component only needs to be present in 90% or more of the interface between the bonding layer 4 and the ceramic substrate 2. The interface with the ceramic substrate 2 refers to the area of the surface of the ceramic substrate 2 where the bonding layer 4 is provided. Areas on the surface of the ceramic substrate 2 where the bonding layer 4 is not provided are not counted. The layer containing titanium as a main component can be confirmed by EDX (energy dispersive X-ray) analysis. An arbitrary cross section of the bonded body 1 is subjected to EDX analysis. In the EDX analysis, an area within a measurement region in the bonding layer 4 is analyzed. The measurement region is an area of 200 μm in length × thickness. If a layer containing titanium as a main component is observed on the surface of the ceramic substrate 2 over 180 μm (= 200 μm × 90%) or more of the measurement region, it can be considered that a layer containing titanium as a main component is present. Furthermore, by performing area analysis using EDX analysis, it is possible to analyze components other than Ti contained in the layer mainly composed of titanium. For example, if nitrogen is detected by area analysis, it is considered that the layer mainly composed of titanium contains Ti nitride. Furthermore, when it is difficult to distinguish the boundary between the ceramic substrate 2 and the bonding layer 4, TEM (transmission electron microscope) analysis is used. Based on the results of the TEM analysis, it is effective to perform EDX point analysis of the bonding layer 4 to detect Ti and N. Elements other than nitrogen can also be detected by a similar method.
[0010] The thickness of the first region 5 is determined as the width between the points of the titanium-based layer closest to the ceramic substrate 2 and the farthest from the titanium-based layer within the measurement region. The titanium-based layer is formed along the surface of the ceramic substrate 2. There are minute irregularities on the surface of the ceramic substrate 2. For this reason, the thickness of the first region 5 is determined by the method described above. Since the thickness of the first region 5 is determined by this method, the first region 5 also includes regions other than the titanium-based layer. Furthermore, within the measurement region, a line that passes through the closest point and is parallel to the surface direction is defined as the boundary line between the ceramic substrate 2 and the first region 5. The surface direction is a direction perpendicular to the thickness direction that connects the ceramic substrate 2 and the bonding layer 4. The boundary line between the ceramic substrate 2 and the first region 5 is called the first boundary line. Within the measurement area, a line that passes through the farthest point and is parallel to the surface direction is defined as the boundary line between the first area 5 and the second area 6. The boundary line between the first area 5 and the second area 6 is called the second boundary line. Therefore, the thickness of the first area 5 is the width between the first boundary line and the second boundary line. The thickness of the second region 6 is the width from the second boundary line to the boundary between the bonding layer 4 and the copper plate 3. The boundary between the bonding layer 4 and the copper plate 3 is the furthest point (the furthest point from the ceramic substrate 2) where the components of the bonding layer are connected and contact the copper plate 3 within the measurement region. From the vicinity of the interface between the second region 6 and the copper plate 3 to the copper plate 3, the detected amount of the components of the bonding layer drops sharply, and the components of the bonding layer become discontinuous. A line that passes through the furthest point where the components of the bonding layer are connected and contact the copper plate 3 within the measurement region and is parallel to the surface direction is called the third boundary line. Therefore, the thickness of the second region 6 is the width from the second boundary line to the third boundary line. Within the measurement region, there is a region where the components constituting the bonding layer 4 are connected to the first region 5. The point where this region contacts the copper plate 3 is the point where the components of the bonding layer 4 are connected and contact the copper plate 3.
[0011] For example, the case where the components constituting the bonding layer 4 are Ag (silver), Cu (copper), Sn (tin), and Ti (titanium) will be described. The components of the bonding layer 4 being connected means that one or more mixed components selected from Ag, Cu, Sn, and Ti are connected from the first region 5 to the copper plate 3. The mixed components mean that Ag, Cu, Sn, and Ti are mixed as single components or mixed as an alloy. Therefore, even if the components constituting the bonding layer 4 are diffused into the copper plate 3, if they are not connected, they are not counted as the third boundary line. The term "not being connected" means that the components of the bonding layer are distributed in a discontinuous state. In addition, when it is not possible to distinguish between the Cu constituting the bonding layer 4 and the Cu of the copper plate 3, the third boundary line is counted with other components.
[0012] The bonded body according to the embodiment is characterized in that, when the Ti concentration in a range of 200 μm × thickness of each measurement area of the first region 5 and the second region 6 is measured by EDX, the ratio M1 / M2 of the Ti concentration M1 at % in the first region 5 to the Ti concentration M2 at % in the second region 6 is 0.1 or more and 5 or less. The ratio of Ti concentration, M1 / M2, being 0.1 or more and 5 or less, indicates that Ti is distributed relatively more in the second region 6. The active metal bonding method is a bonding technique using Ti. In the active metal bonding method, as shown in Patent Document 1 and Patent Document 2, a titanium nitride (TiN) layer is formed. This titanium nitride layer corresponds to a layer mainly composed of titanium. Conventionally, Ti was concentrated in the titanium nitride layer, so the Ti concentration in the region corresponding to the second region 6 was low. For this reason, conventionally, M1 / M2 was 20 or more. The titanium nitride layer is a hard layer. It has been found that a difference in hardness between the first region and the second region can adversely affect the TCT characteristics. In addition, when M1 / M2 is less than 0.1, the amount of Ti in the first region 5 is small. When the amount of Ti in the first region 5 is small, the amount of titanium nitride is insufficient, so the bonding strength may decrease. In Patent Document 1 and Patent Document 2, the layer mainly composed of titanium contains titanium nitride (TiN). This is because the nitride ceramic substrate reacts with Ti. Therefore, when an oxide ceramic substrate is used, titanium oxide is formed. In the active metal bonding method, an active metal brazing material containing Ag or Cu as the main component and Ti as the active metal is used. Sn (tin) or In (indium) may also be added to the active metal brazing material. Among active metal brazing materials, Ti is a relatively hard material. Therefore, by controlling the Ti concentration in the bonding layer, the hardness in the bonding layer can be made more uniform. Therefore, M1 / M2 is preferably 0.1 to 5, and more preferably 0.5 to 4.
[0013] For the EDX analysis, SEM-EDX is used. For the SEM, JSM-IT100 manufactured by JEOL Ltd. or a device having equivalent performance is used. For the EDX, EX-9440IT4L11 manufactured by JEOL Ltd. or a device having equivalent performance is used. First, an area analysis is performed by EDX in a measurement area of 200 μm × thickness. The measurement area is set to 200 μm × thickness because it is a suitable range for investigating the distribution of the bonding layer components. If the measurement area is smaller than 200 μm, it is easily affected by the diffusion state of the material contained in the bonding layer to the copper plate. The grain size of the copper particles contained in the copper plate is about 10 to 1000 μm. The grain boundary of the copper plate becomes the route for the diffusion of the material contained in the bonding layer. In order to suppress the influence of the easy-to-diffuse and difficult-to-diffuse places on the analysis, it is preferable that the measurement area is 200 μm. If the measurement area is larger than 200 μm, the variation in Ti concentration cannot be measured. As described later, the measurement region is preferably 200 μm in order to measure the variation in Ti concentration within the second region. M1 / M2 is calculated as the average value of three arbitrary positions.
[0014] The variation in Ti concentration in the second region 6 is preferably within ±20%. The variation in Ti concentration in the second region 6 is the difference between the Ti concentration in the second region 6 in a first measurement region and the Ti concentration in the second region 6 in another measurement region. The Ti concentration in the first measurement region is designated as M2a, and the Ti concentration in the other measurement region is designated as M2b. The variation V of the Ti concentration in the second region 6 is calculated by V(%)=[(M2a-M2b) / M2a]×100. The TCT characteristics can be improved by suppressing the variation in the Ti concentration within the second region 6 as well as the Ti concentrations in the first region 5 and the second region 6. For this reason, it is preferable that the variation in the Ti concentration within the second region 6 is within ±20%, and more preferably within ±10%.
[0015] The thickness of the first region 5 is preferably 5 μm or less. The first region 5 includes a layer mainly composed of titanium. If the first region 5 is thicker than 5 μm, titanium may accumulate in the first region 5 too much, causing M1 / M2 to exceed 5. The thickness of the second region is preferably 5 μm or more and 70 μm or less. It is preferable to control the Ti concentration of the second region 6 having a predetermined thickness.
[0016] The Ti concentration in the second region 6 is preferably in the range of 0.5 at% to 15 at%. If the Ti concentration in the second region 6 is less than 0.5 at%, the amount of Ti in the second region 6 may be insufficient. If the amount of Ti is small, the variation of the Ti concentration in the second region 6 tends to increase. If the Ti concentration is more than 15 at%, M1 / M2 tends to be less than 0.1. For this reason, the Ti concentration in the second region 6 is preferably 0.5 at% to 15 at%, and more preferably 1 at% to 10 at%. When measuring the Ti concentration in the second region 6 in at%, the value is obtained excluding O (oxygen), N (nitrogen), and C (carbon). As described later, metal components such as Ag and Cu exist in the M2 region. In order to control the abundance ratio with metal components other than Ti, at% is effective.
[0017] The copper plate preferably has a thickness of 0.6 mm or more.The ceramic substrate is preferably any one selected from a silicon nitride substrate and an aluminum nitride substrate. A copper plate or a copper alloy plate can be used for the copper plate 3. The copper plate 3 is preferably made of oxygen-free copper. As specified in JIS-H-3100 (ISO1337, etc.), oxygen-free copper has a copper purity of 99.96 wt% or more. The copper plate 3 is used as a circuit section or a heat sink. The current carrying capacity and heat dissipation properties can be improved by increasing the thickness of the copper plate 3. For this reason, the thickness of the copper plate 3 is preferably 0.6 mm or more, more preferably 0.8 mm or more.
[0018] The ceramic substrate 2 may be a silicon nitride substrate, an aluminum nitride substrate, an aluminum oxide substrate, an aluminium substrate, or the like. The thickness of the ceramic substrate 2 is preferably 0.1 mm or more and 1 mm or less. If the substrate thickness is less than 0.1 mm, the strength may be reduced. If the substrate thickness is more than 1 mm, the ceramic substrate may become a thermal resistor, which may reduce the heat dissipation of the bonded body. The three-point bending strength of the silicon nitride substrate is preferably 600 MPa or more. The thermal conductivity is preferably 80 W / m·K or more. By increasing the strength of the silicon nitride substrate, the thickness of the substrate can be reduced. For this reason, the three-point bending strength of the silicon nitride substrate is preferably 600 MPa or more, and more preferably 700 MPa or more. This allows the thickness of the silicon nitride substrate to be reduced to 0.40 mm or less, and even 0.30 mm or less. The three-point bending strength of an aluminum nitride substrate is about 300 to 450 MPa. On the other hand, the thermal conductivity of an aluminum nitride substrate is 160 W / m·K or more. Since the strength of an aluminum nitride substrate is low, the substrate thickness is preferably 0.60 mm or more. The three-point bending strength of aluminum oxide substrates is about 300 to 450 MPa, but aluminum oxide substrates are inexpensive. The three-point bending strength of Al2O3 substrates is high at about 550 MPa, but their thermal conductivity is about 30 to 50 W / m K. The ceramic substrate 2 is preferably either a silicon nitride substrate or an aluminum nitride substrate. The silicon nitride substrate and the aluminum nitride substrate are nitride ceramic substrates. The nitride ceramic reacts with the active brazing metal material containing Ti to form titanium nitride. This makes it easier to form a layer mainly composed of titanium nitride in the first region 5. Furthermore, the oxide ceramic reacts with the active brazing metal material containing Ti to form titanium oxide, which makes it easier to form a layer mainly composed of titanium oxide in the first region 5. The oxide ceramic is, for example, an aluminum oxide substrate or an aluminium substrate.
[0019] It is preferable that the copper plates 3 are disposed on both sides of the ceramic substrate 2. By bonding the copper plates to both sides, warping of the bonded body can be suppressed. The second region preferably contains one or two elements selected from silver and copper, and preferably contains one or two elements selected from tin and indium. In order to include silver or copper in the second region 6, it is effective to include silver or copper in the active brazing material. In order to include tin or indium in the second region 6, it is effective to include tin or indium in the active brazing material. The active metal brazing material composition preferably contains 0% to 70% by mass of Ag (silver), 15% to 85% by mass of Cu (copper), and 1% to 15% by mass of Ti (titanium) or TiH2 (titanium hydride). When both Ti and TiH2 are used, the total of these is within the range of 1 to 15% by mass. When both Ag and Cu are used, it is preferable that Ag is 20 to 60% by mass and Cu is 15 to 40% by mass. If necessary, the active metal brazing material may contain one or two elements selected from Sn (tin) and In (indium) in an amount of 1% by mass to 50% by mass. The content of Ti or TiH2 is preferably 1 to 15% by mass. If necessary, the active metal brazing material may contain 0.1% by mass to 2% by mass of C (carbon). The ratio of the active metal brazing material composition is calculated with the total of the mixed raw materials being 100% by mass. For example, if the active metal brazing material is composed of three elements, Ag, Cu, and Ti, then Ag+Cu+Ti=100% by mass. If the active metal brazing material is composed of four elements, Ag, Cu, TiH2, and In, then Ag+Cu+TiH2+In=100% by mass. If the active metal brazing material is composed of five elements, Ag, Cu, Ti, Sn, and C, then Ag+Cu+Ti+Sn+C=100% by mass.
[0020] Ag or Cu is a component that becomes the base material of the brazing material. Sn or In has the effect of lowering the melting point of the brazing material. C (carbon) has the effect of controlling the fluidity of the brazing material and controlling the structure of the bonding layer by reacting with other components. For this reason, the components of the brazing material include Ag-Cu-Ti, Ag-Cu-Sn-Ti, Ag-Cu-Ti-C, Ag-Cu-Sn-Ti-C, Ag-Ti, Cu-Ti, Ag-Sn-Ti, Cu-Sn-Ti, Ag-Ti-C, Cu-Ti-C, Ag-Sn-Ti-C, and Cu-Sn-Ti-C. In may be used instead of Sn. Both Sn and In may be used. Instead of Sn or In, low melting point metals such as Bi (bismuth), Sb (antimony), and Ga (gallium) may be used.
[0021] The melting point of the active metal brazing material is preferably 700° C. or less. By lowering the melting point of the brazing material, the joining temperature can be lowered. By lowering the joining temperature, the Ti concentration in the first region 5 and the Ti concentration in the second region 6 can be controlled. In the DSC curve of the active metal brazing material, the largest endothermic peak is preferably in the range of 550° C. to 700° C. The temperature at which the largest endothermic peak occurs in the DSC curve is defined as the melting point of the active metal brazing material.
[0022] DSC curves are obtained by measuring endothermic and exothermic reaction peaks using a differential scanning calorimeter (DSC). Negative peaks are endothermic reactions, and positive peaks are exothermic reactions. The DSC curve is measured using a temperature profile consisting of a heating step, a holding step at a constant temperature, and a cooling step. In the temperature profile, the heating step is to raise the temperature from room temperature to 500°C at a heating rate of 5°C / min. Next, the heating step is to hold at 500°C for 60 minutes. After that, the heating step is to raise the temperature to 845°C at a heating rate of 5°C / min. In the holding step, the temperature is held at 845°C for 30 minutes. In the cooling step, the temperature is lowered from 845°C to room temperature at a heating rate of 5°C / min. As the DSC, a NETZSCH TGA-DSC simultaneous thermal analyzer STA449-F3-Jupiter or an apparatus with equivalent performance is used. The measurement is performed in an Ar (argon) flow by dropping an appropriate amount of brazing material into an alumina container. It is necessary to prevent the brazing material from reacting with the atmosphere by performing the measurement in an Ar atmosphere.
[0023] During the temperature rise process of the DCS curve, the temperature at which the largest endothermic peak is detected in the temperature range of 550°C to 800°C is defined as the melting point. The melting point of the brazing material being 700°C or less means that the largest endothermic peak is in the range of 550 to 700°C. Even if there is a negative peak below 550°C, it does not need to be counted as an endothermic peak. The endothermic reaction is caused by the melting or decomposition of the active metal brazing material. For example, if titanium hydride (TiH2) is used as the active metal, a negative peak is detected around 500°C. This peak is the peak when TiH2 decomposes into Ti and H.
[0024] The bonded body as described above is suitable for a ceramic copper circuit board. A circuit structure is provided on the copper plate disposed on at least one surface of the ceramic substrate. In this way, a ceramic copper circuit board using the bonded body according to the embodiment is obtained. FIG. 3 shows an example of a ceramic copper circuit board according to an embodiment. In FIG. 3, 7 is a circuit part. 8 is a heat sink. 10 is a ceramic copper circuit board. The circuit part 7 is formed by providing a circuit structure to the copper plate 3 on the front side. The heat sink 8 is formed by processing the copper plate 3 on the back side. In FIG. 3, two circuit parts 7 are provided. The ceramic copper circuit board according to the embodiment is not limited to the structure shown in the figure. The number and shape of the circuit parts 7 are arbitrary. The circuit part 7 may be formed by providing a circuit structure to the copper plates 3 on both sides. The side of the circuit part 7 or the side of the heat sink 8 may be inclined with respect to the thickness direction. A bonding layer protruding part may be provided in which the bonding layer 4 protrudes from the end of the circuit part 7 or the end of the heat sink 8. In the ceramic copper circuit board 10 according to the embodiment, the Ti distribution in the bonding layer 4 is controlled, so that the TCT characteristics can be improved.
[0025] FIG. 4 is a diagram showing another example of a ceramic copper circuit board according to an embodiment. The ceramic substrate may have a through hole. The copper plate on the front side and the copper plate on the back side may be electrically connected through the through hole. FIG. 4 shows an example of a ceramic copper circuit substrate having a through hole. FIG. 4 is a cross-sectional view of a portion in which a through hole is provided. In FIG. 4, 10 is a ceramic copper circuit substrate. 2 is a silicon nitride substrate. 4 is a bonding layer. 7a is a circuit portion on the front side. 7b is a circuit portion on the back side. 9 is a through hole. In FIG. 4, the circuit portion 7a and the circuit portion 7b are electrically connected through the through hole 9. In FIG. 4, a plurality of through holes 9 respectively connect a plurality of circuit portions 7a and a plurality of circuit portions 7b. The embodiment is not limited to such a structure. In the ceramic copper circuit substrate 10, the through hole 9 may be provided only for a portion of the plurality of circuit portions 7a. The through hole 9 may be provided only for a portion of the circuit portion 7b. The inside of the through hole 9 is preferably filled with the same material as the bonding layer 4. The internal structure of the through hole 9 is not particularly limited as long as it can electrically connect the circuit part on the front side to the circuit part on the back side. For this reason, a metal thin film may be provided only on the inner wall of the through hole 9. On the other hand, by filling it with the same material as the bonding layer 4, the bonding strength can be improved.
[0026] FIG. 5 is a diagram illustrating an example of a semiconductor device according to an embodiment. The ceramic copper circuit board according to the embodiment is suitable for a semiconductor device. In the semiconductor device, a semiconductor element is mounted on the copper plate of the ceramic copper circuit board via a bonding layer. FIG. 5 shows an example of a semiconductor device. In FIG. 5, 10 is a ceramic copper circuit board. 7 is a circuit part. 8 is a heat sink. 20 is a semiconductor device. 21 is a semiconductor element. 22 is a bonding layer. 23 is a wire bonding. 24 is a metal terminal. In FIG. 5, a semiconductor element 21 is bonded onto a circuit part of a ceramic copper circuit board 10 via a bonding layer 22. Similarly, a metal terminal 24 is bonded via a bonding layer 22. Adjacent circuit parts are electrically connected to each other by a wire bonding 23. In FIG. 5, in addition to the semiconductor element 21, a wire bonding 23 and a metal terminal 24 are bonded to the ceramic copper circuit board 10. The semiconductor device according to the embodiment is not limited to such a structure. For example, only one of the wire bonding 23 and the metal terminal 24 may be provided. A plurality of semiconductor elements 21, wire bonding 23, and metal terminals 24 may be provided on the front circuit portion. A circuit structure may be provided on the copper plate on the rear side, and the semiconductor elements 21, wire bonding 23, and metal terminals 24 may be joined to the circuit structure. Various shapes such as a lead frame shape or a convex shape may be applied to the metal terminals 24. By using the bonded body according to the embodiment in the above-mentioned ceramic copper circuit board or semiconductor device, the TCT characteristics can be improved.
[0027] Next, a method for producing the bonded body according to the embodiment will be described. The method for producing the bonded body according to the embodiment is not limited as long as the bonded body according to the embodiment has the above-mentioned configuration. Here, an example of a method for obtaining the bonded body according to the embodiment with a high yield will be described. First, prepare a ceramic substrate 2. The ceramic substrate 2 is a silicon nitride substrate, an aluminum nitride substrate, an aluminum oxide substrate, an aridil substrate, etc. The aridil substrate is a substrate made of a mixture of aluminum oxide and zirconium oxide. A copper plate or a copper alloy plate can be used for the copper plate 3. The copper plate 3 is preferably oxygen-free copper. As specified in JIS-H-3100, oxygen-free copper has a copper purity of 99.96 wt% or more.
[0028] Next, an active metal brazing material paste containing Ti is prepared. The active metal brazing material containing Ti preferably contains one or two selected from Ag and Cu as components other than Ti. The active metal brazing material preferably contains one or two selected from Sn and In. The active metal brazing material may contain C (carbon). The active metal brazing material may contain a compound such as TiH2 as Ti. The composition ratio (mass%) of each component is as described above. In order to control the melting point of the active metal brazing material, it is effective to control the composition, the particle size of the raw material powder, etc. As mentioned above, Sn or In has the effect of lowering the melting point of the brazing material. It is effective to make the powder particle size of Sn or In the components constituting the brazing material the largest. For example, when using an Ag-Cu-Sn-Ti brazing material, the particle size of Sn powder is made the largest among Ag powder, Cu powder, Sn powder, and Ti powder. Sn powder easily reacts with other brazing material components. By increasing the particle size of Sn powder, it becomes easier for Sn powder to come into contact with other components. This can lower the melting point of the brazing material. The same is true when In is used instead of Sn. It is effective to increase the particle size of the components that have the effect of lowering the melting point. In addition, lowering the joining temperature can reduce the load on the joining equipment.
[0029] The powders of the components of the active metal brazing material are mixed to prepare a uniformly dispersed mixed powder. The mixing step of the powders of the components is preferably carried out for 10 hours or more. Next, the mixed powder is mixed with a binder and a solvent to prepare an active metal brazing paste. It is preferable that the mixing process of the mixed powder and the binder, etc. is also carried out for 10 hours or more. The active metal brazing paste is applied to at least one of a ceramic substrate or a copper plate. The thickness of the active metal brazing paste layer is preferably 5 μm or more and 80 μm or less. The thickness of the active metal brazing paste layer is the thickness after the applied paste is dried. If the thickness is less than 5 μm, the bonding strength may decrease. If the thickness is more than 80 μm, the thermal stress in the bonding process may increase, and the bonded body may be warped. For this reason, the thickness of the active metal brazing paste layer is preferably 5 μm or more and 80 μm or less, and more preferably 10 μm or more and 50 μm or less.
[0030] After the step of applying the active metal brazing paste, a step of placing a member not coated with the paste on the member coated with the paste is performed. For example, when the active metal brazing paste is applied to a ceramic substrate, a copper plate is placed on the ceramic substrate. The active metal brazing paste may be applied to both sides of the ceramic substrate, and a copper plate may be placed on each side. The active metal brazing paste may be applied to the copper plate, and the ceramic substrate may be placed on the copper plate.
[0031] Next, a bonding process is performed in which the bonding temperature is 800°C or less. The bonding temperature is the maximum temperature that is maintained for a certain period of time. A high bonding temperature promotes grain growth of the copper crystal grains that make up the copper plate. In the conventional active metal bonding method, the bonding temperature was about 850°C. When the bonding temperature exceeds 800°C, the grain growth of the copper plate increases. When the grain growth of the copper plate increases, large crystal grains with a major axis exceeding 400 μm tend to be formed. The bonding temperature is preferably 800°C or less, more preferably 700°C or less. The lower limit of the bonding temperature is not particularly limited, but 500°C or more is preferable. If the bonding temperature is low, the reliability of the bonding may decrease. For this reason, the bonding temperature is preferably 500°C or more and 800°C or less, more preferably 550°C or more and 700°C or less. The holding time of the bonding temperature is preferably 100 minutes or less, more preferably 30 minutes or less. When bonding is performed at a temperature exceeding 800°C, the heating rate is preferably 20°C / min or more. By increasing the heating rate, the amount of heat from room temperature to the bonding temperature can be reduced. This allows the same effect as that of a bonding temperature of 800°C or less to be obtained. In addition, the bonding temperature can be from over 800°C to 950°C or less. There is no particular limit to the upper limit of the heating rate, but it is preferably 100°C / min or less. The heating rate from room temperature to the bonding temperature is preferably 20 to 100°C / min, more preferably 30 to 70°C / min. If the heating rate exceeds 100°C / min, control may become difficult. In addition, the temperature drop rate from the bonding temperature to room temperature is preferably within the range of 20 to 100°C / min. By increasing the heating rate and temperature drop rate, the amount of heat can be made equivalent to that of 800°C or less. The atmosphere during the bonding step is preferably a vacuum or a nitrogen atmosphere. The pressure in a vacuum is 10 -3 The pressure is preferably not more than 10 Pa. In a vacuum, it is possible to prevent Ti in the brazing material from nitriding before it reacts with the ceramic substrate. A nitrogen atmosphere refers to an atmosphere containing 90 vol% to 100 vol% nitrogen. If nitrogen is present in the atmosphere during the joining process, it is thought that Ti will become titanium nitride before reacting with the ceramic substrate. If the Ti content in the brazing material is 6 mass% or more, Ti and the ceramic substrate can react sufficiently even in a nitrogen atmosphere. The bonding process may be either a batch type or a continuous type. In the batch type, the ceramic substrate and the copper plate are placed in a storage container and subjected to heat treatment. In the continuous type, the ceramic substrate and the copper plate are placed on a conveyer belt and subjected to heat treatment while moving. The batch type is suitable for bonding processes in a vacuum. The continuous type is suitable for bonding processes in a nitrogen atmosphere. In the batch type, the bonding temperature can be held for a short time. In the continuous type, the bonding temperature is held for a long time, but mass productivity is improved because heat treatment can be performed continuously. Batch type bonding equipment is sometimes called a batch furnace, and continuous type bonding equipment is sometimes called a continuous furnace.
[0032] The Ti concentration in the bonding layer 4 can be controlled by lowering the bonding temperature or shortening the time for which the bonding temperature is maintained. As mentioned above, the components of the active metal brazing material are mixed uniformly. Therefore, at the stage of the active metal brazing material paste layer, Ti is uniformly dispersed. Also, at the stage of the active metal brazing material paste layer, a layer mainly composed of titanium is not formed. By carrying out the bonding process, a layer mainly composed of titanium is formed. When the bonding temperature is as high as 850°C as in the conventional method, Ti gathers in the layer mainly composed of titanium. As a result, Ti aggregates in the first region 5, and the M1 / M2 ratio becomes about 10. By setting the bonding temperature at 800°C or less, or even at least 550°C and at most 700°C, M1 / M2 can be controlled. By lowering the bonding temperature, the amount of Ti that gathers in the titanium-based layer can be reduced, and Ti can remain in the second region 6. Similarly, by setting the bonding temperature holding time to 60 minutes or less, or even at most 30 minutes, the amount of Ti that gathers in the titanium-based layer can be reduced, and Ti can remain in the second region 6. In addition, by increasing the content of Ti or TiH2 as a component of the active metal brazing material (for example, to 5 mass% or more), it is also possible to increase the amount of Ti in the second region. As a result, M1 / M2 can be set within the range of 0.1 to 5. Furthermore, by uniformly mixing the mixed powder of the active brazing metal material, the variation in Ti concentration in the second region 6 can be kept within ±20%. In other words, in the case of a batch type process carried out in a vacuum, it is effective to lower the bonding temperature to 800°C or less, or even 700°C or less. In the case of a continuous process carried out in a nitrogen atmosphere, the process may be carried out at a temperature exceeding 800°C. The time for which the joining temperature is held can be shortened by increasing the rate of temperature rise or fall. This reduces the amount of Ti that collects in the layer mainly composed of titanium, allowing Ti to remain in the second region 6. In addition, an active metal brazing material that does not contain Ag is effective for the continuous process carried out in a nitrogen atmosphere. In addition, in the bonded body that has undergone the bonding process, TiSi, CuSn, and TiSn are formed in the second region 6. TiSi is formed by the reaction of titanium and silicon. CuSn is formed by the reaction of copper and tin. TiSn is formed by the reaction of titanium and tin. The atomic ratio of each compound is not limited to 1:1. When the bonding process is performed in a vacuum, the mass ratio of the compounds in the second region 6 preferably satisfies TiSi>TiSn and CuSn>TiSn. Among TiSi, CuSn, and TiSn, CuSn has the lowest melting point. In the bonding process in a vacuum, the temperature rise rate is slow, about 1 to 2°C / min. By increasing the amount of CuSn formed during the slow temperature rise process, the amount of Ti in the second region 6 can be controlled.
[0033] It is preferable that the length and width of the bonded body be the same as that of the ceramic substrate 2 and the copper plate 3. The thermal conductivity of the ceramic substrate 2 is preferably 60 W / m·K or more. It is preferable that the copper plates 3 are bonded to both sides of the ceramic substrate 2. The theoretical value of the thermal conductivity of copper is about 398 W / m·K. By making the length and width of the ceramic substrate 2 and the length and width of the copper plate 3 the same, the heat is transferred to the active metal brazing paste layer uniformly. Similarly, the heat transfer can be made uniform by increasing the thermal conductivity of the ceramic substrate 2 and placing the copper plates 3 on both sides. This makes it possible to keep the variation in the Ti concentration in the second region 6 within ±20%, or even ±10%. Even if the size of the bonded body 1 becomes large, the variation in the Ti concentration can be suppressed. Therefore, even if the size of the bonded body becomes large, such as 200 mm or more in length and 200 mm or more in width, the variation in the Ti concentration can be suppressed. Even if the length or width of the joined body is 200 mm or more, the amount of warping of the joined body can be kept to 0.1 mm or less. Even if the thickness of the copper plate on the front side is different from that of the copper plate on the back side, the amount of warping of the joined body can be kept to 0.1 mm or less.
[0034] The above steps allow the manufacture of a bonded body in which a ceramic substrate and a copper plate are bonded. If necessary, a circuit section 7 or a heat sink 8 structure is provided to the copper plate 3. By providing the circuit section 7, the bonded body 1 becomes a ceramic copper circuit board 10. Since the Ti concentration in the first region 5 and the second region 6 is controlled, the TCT characteristics can be improved. In addition, since the size of the bonded body 1 can be increased, it is a bonded body suitable for multi-cavity production. Multi-cavity production is a method of cutting a large bonded body to obtain small bonded bodies. There are also methods of dividing the bonded body or dividing the ceramic copper circuit board. To make it easier to divide, a scribing process may be performed.
[0035] (Example) (Examples 1 to 15, Comparative Examples 1 to 3) As the ceramic substrates, silicon nitride substrates and aluminum nitride substrates shown in Table 1 were prepared.
[0036] [Table 1]
[0037] Next, we prepared the copper plates shown in Table 2. All of the copper plates were oxygen-free copper.
[0038] [Table 2]
[0039] Next, the active metal brazing materials shown in Table 3 were prepared. For active metal brazing materials 1 to 3, the Sn powder had the largest particle size. For active metal brazing material 4, the Ag powder had the largest particle size. The components of brazing materials 1 to 3 and 5 to 6 were mixed for 10 hours or more. The components of brazing material 4 were mixed for 5 hours. The melting points of the brazing materials were determined by measuring the DSC curves as described above.
[0040] [Table 3]
[0041] Next, a bonding process was carried out using a ceramic substrate, a copper plate, and an active metal brazing material. The length and width of the copper plate were adjusted to match the length and width of the ceramic substrate. Table 4 shows the atmosphere used in the bonding process. -3 The bonding process was performed in a vacuum of 100 Pa or less, and was indicated as "vacuum." The bonding process was performed in a nitrogen atmosphere of 98 vol% or more nitrogen, and was indicated as "nitrogen." For the bonding process in which the bonding temperature was 800°C or less, the heating rate from room temperature to the bonding temperature and the heating rate from the bonding temperature to room temperature were set within the range of 1 to 10°C / min. For Example 13 and Example 14 in which the bonding temperature exceeded 800°C, the heating rate from room temperature to the bonding temperature and the heating rate from the bonding temperature to room temperature were set within the range of 30 to 70°C / min. The bonding process in a vacuum was performed in a batch furnace. The bonding process in a nitrogen atmosphere was performed in a continuous furnace. The combinations of the materials are as shown in Table 4.
[0042] [Table 4]
[0043] The bonded bodies according to the examples and the comparative examples were produced by the above steps. An arbitrary cross section of each bonded body was subjected to EDX analysis. As a result, the thickness of the first region, the thickness of the second region, and the Ti concentration of each region were analyzed. For the EDX analysis, an area analysis was performed with a measurement region of 200 μm length × thickness. The average values of three arbitrary locations are shown as M1 and M2. The Ti concentration was calculated in at%. When calculating in at%, the total of the components excluding O (oxygen), N (nitrogen), and C (carbon) was taken as 100 at%. The other conditions were as described above. The results are shown in Table 5.
[0044] [Table 5]
[0045] As can be seen from the analysis results of Examples 1 to 15 shown in Table 5, in the joined bodies according to the examples, M1 / M2 was in the range of 0.1 to 5. Furthermore, in the first region, a layer mainly composed of titanium, in which TiN was in the range of 65 mass % to 100 mass %, was observed. In the second region 6 of the bonded body bonded in a vacuum, the mass ratios of TiSi>TiSn and CuSn>TiSn were satisfied. On the other hand, in the bonded bodies bonded in a nitrogen atmosphere, bonded bodies that did not necessarily satisfy such relationships were observed. In addition, the amount of warping of the bonded bodies according to the examples and comparative examples was measured. The amount of warping of the bonded bodies was measured on the long side. Bonded bodies with a warping amount on the long side of 0.1 mm or less were designated as good products (◯), and bonded bodies with a warping amount on the long side exceeding 0.1 mm were designated as defective products (×). Bonded bodies were produced for each example, and the bonded body with the worst value out of 50 bodies for each example was displayed. The results are shown in Table 6.
[0046] [Table 6]
[0047] As can be seen from Table 6, the amount of warpage of the bonded bodies according to the examples was small, at 0.1 mm or less. Even when the thicknesses of the front and back copper plates were different, as in Examples 7, 8, 10, and 12, the amount of warpage of the bonded bodies could be reduced. In contrast, the amount of warpage of the bonded bodies according to the comparative examples exceeded 0.1 mm.
[0048] Next, each bonded body was etched to form a circuit part and a heat sink. Each bonded body was divided into four pieces, and a large number of ceramic copper circuit boards were obtained. The shapes of the circuit part and the heat sink were the same between the embodiment and the comparative example. Twelve bonded bodies after division were prepared. The TCT characteristics of each ceramic copper circuit board were investigated. The TCT test consisted of one cycle of -40°C x 30 min → room temperature x 10 min → 170°C x 30 min → room temperature x 10 min. The bonded bodies using silicon nitride substrates were tested for 2000 and 3000 cycles. The bonded bodies using aluminum nitride substrates were tested for 300 and 600 cycles. The 12 joints with no defects were rated as the best product (◎), those with one defect were rated as good products (◯), and those with two or more defects were rated as poor products (×). The results are shown in Tables 7 and 8.
[0049] [Table 7]
[0050] [Table 8]
[0051] The ceramic copper circuit board according to the embodiment had good TCT characteristics. It was found that the TCT characteristics were improved by controlling the Ti concentration in the bonding layer. In addition, even if the bonded body was enlarged, the Ti concentration could be controlled, so the reliability was good even when multiple pieces were produced. In contrast, in the comparative example, the Ti concentration ratio M1 / M2 in the bonding layer was outside the range of 0.1 to 5, so the TCT characteristics varied. This is thought to be due to the influence of Ti concentration variations as the bonding body became larger. For this reason, it was found that the method is not suitable for multiple-cavity production.
[0052] Although some embodiments of the present invention have been illustrated above, these embodiments are presented as examples and are not intended to limit the scope of the invention. These novel embodiments can be implemented in various other forms, and various omissions, substitutions, modifications, etc. can be made without departing from the gist of the invention. Modifications of these embodiments are included in the scope and gist of the invention, and are included in the scope of the invention and its equivalents described in the claims. In addition, the above-mentioned embodiments can be implemented in combination with each other.
Claims
1. A silicon nitride substrate; Copper plate and a bonding layer disposed on at least one surface of the silicon nitride substrate and bonding the silicon nitride substrate and the copper plate; Equipped with The bonding layer contains titanium, The bonding layer is a first region including a titanium-based layer formed at an interface of the bonding layer with the silicon nitride substrate; A second region located between the first region and the copper plate; having When the Ti concentration in a range of 200 μm×thickness of each of the first and second measurement regions is measured by EDX, a ratio M1 / M2 of a titanium concentration M1 at % in the first region to a titanium concentration M2 at % in the second region is 0.5 or more and 5 or less, the titanium concentration M2 of the second region is within the range of 0.5 at% to 15 at%; A bonded body characterized in that when a plurality of the measurement regions are set in the second region and the Ti concentration of each of the measurement regions is measured by EDX, the variation in Ti concentration between the plurality of measurement regions is within ±20%.
2. 2. The bonded structure according to claim 1, wherein the first region has a thickness of 5 μm or less.
3. 3. The bonded body according to claim 1, wherein the second region has a thickness of 5 μm or more and 70 μm or less.
4. 4. The joint body according to claim 1, wherein the second region contains TiSi, CuSn, and TiSn.
5. 5. The joined body according to claim 1, wherein the copper plate has a thickness of 0.6 mm or more.
6. 6. The joined body according to claim 1, wherein the second region contains one or two kinds selected from silver and copper.
7. 7. The bonded body according to claim 1, wherein the copper plates are disposed on both sides of the silicon nitride substrate.
8. A joint body according to any one of claims 1 to 7, A ceramic copper circuit board, characterized in that a circuit structure is provided on the copper plate disposed on at least one surface of the silicon nitride substrate.
Citation Information
Patent Citations
Brazing material for ceramic substrates, and ceramic circuit board using the same
JP2004314161A
Braze for ceramic substrate and ceramic circuit board using the same
JP2005112677A
Ceramic circuit board and method for manufacturing ceramic circuit board
WO2017213207A1
Ceramic circuit board, method for manufacturing ceramic circuit board, and module using ceramic circuit board
WO2018199060A1
ceramic circuit board
JP4077888B2